Molecular Basis of a Bacterial Consortium: Interspecies Catabolism of Atrazine - de Souza, Mervyn L. (American Society for Microbiology, 1998)
Pseudomonas sp. strain ADP contains the genes, atzA, -B, and -C, that encode three enzymes which metabolize atrazine to cyanuric acid. Atrazine-catabolizing pure cultures isolated from around the world contain genes homologous to atzA, -B, and -C. The present study was conducted to determine whether the same genes are present in an atrazine-catabolizing bacterial consortium and how the genes and metabolism are subdivided among member species. The consortium contained four or more bacterial species, but two members, Clavibacter michiganese ATZ1 and Pseudomonas sp. strain CN1, collectively mineralized atrazine. C. michiganese ATZ1 released chloride from atrazine, produced hydroxyatrazine, and contained a homolog to the atzA gene that encoded atrazine chlorohydrolase. C. michiganese ATZ1 stoichiometrically metabolized hydroxyatrazine to N-ethylammelide and contained genes homologous to atzB and atzC, suggesting that either a functional AtzB or -C catalyzed N-isopropylamine release from hydroxyatrazine. C. michiganese ATZ1 grew on isopropylamine as its sole carbon and nitrogen source, explaining the ability of the consortium to use atrazine as the sole carbon and nitrogen source. A second consortium member, Pseudomonas sp. strain CN1, metabolized the N-ethylammelide produced by C. michiganese ATZ1 to transiently form cyanuric acid, a reaction catalyzed by AtzC. A gene homologous to the atzC gene of Pseudomonas sp. strain ADP was present, as demonstrated by Southern hybridization and PCR. Pseudomonas sp. strain CN1, but not C. michiganese, metabolized cyanuric acid. The consortium metabolized atrazine faster than did C. michiganese individually. Additionally, the consortium metabolized a much broader set of triazine ring compounds than did previously described pure cultures in which the atzABC genes had been identified. These data begin to elucidate the genetic and metabolic bases of catabolism by multimember consortia.